Community awareness and participation in Argungu Fishing Festival, Kebbi State, Nigeria - T.T. Olubunmi-Ojo; W.O. Adebayo; O.M. Orimaye (Journal of Rural Tourism, 2025)
Purpose - This study aims to evaluate the level of community awareness and participation in the Argungu Fishing Festival in Kebbi State, Nigeria. It seeks to identify key factors influencing local engagement and to propose strategies for strengthening community involvement in order to support heritage preservation and sustainable tourism development.Methodology/Design/Approach - A cross-sectional survey design was employed, integrating primary data collected through self-administered questionnaires, interviews, and field observations with secondary data from government publications. A total of 440 respondents (community members) were sampled. Data analysis was performed using SPSS version 23.Findings - This study indicate that 95% of community respondents were highly aware of the festival, with strong familiarity reported for its major activities. Furthermore, significant relationships were found between the frequency of participation and socio-demographic factors such as age, sex, education, occupation, and marital status (r = 0.106, p < 0.05). In contrast, monthly income did not significantly influence participation (r = 0.07, p > 0.05). These results suggest that cultural attachment and community identity may outweigh economic factors in driving festival engagement.Originality/Value - The study underscores the need for targeted promotional strategies to bridge the awareness gap among non-community participants and enhance overall festival participation. By elucidating the socio-cultural dynamics underlying local engagement, this research contributes valuable insights to the field of tourism. It offers practical recommendations for policymakers and stakeholders seeking to develop sustainable tourism initiatives, ensuring that cultural festivals like the Argungu Fishing Festival can effectively promote both heritage preservation and economic development in Nigeria.